Ti. Ja. Ra. - Ti. Ja. Ra.,Tilakavati (Amrutā, 2007)
Collection of short stories on social themes
Short stories. - Tamil in Tamil-Schr. - Pītāmparaiyar – Paṇakkāri – Navīṉa katāciriyaṉ – Marattaṭik kaṭavuḷ – Pommai yāṉai – Kaṉṉiyiṉ pirārttaṉai – Caṅku mōtiram – Camātāṉam – Rikṣākkāra vēlaṉ – Jōṭikkāḷai
Keywords: Short stories; Tamil